PROTEIN C AND AT III IN ESSENTIAL HYPERTENSION - Bielawiec, M; Kloczko, J; Wojtukiewicz, M; Borowska, M (Thrombosis and Haemostasis, 1987)
Since hypertension is generally accepted as a risk factor for atherosclerosis and, on the other hand, alterations in haemostasis were reported in the disease, we focused our interest on two plasma inhibitors-protein C and antithrombin III, which play critical roles in the regulation of blood clotting process. We studied 19 patients with newly diagnosed essential hypertension at ist and 2ncl degreeof the disease (acc.to WHO criteria). Protein C antigen level was measured by means of ELISA Protein C test (Boehringer Mannheim GmbH).AT III and Factor VIII R:Ag concentrations were measured by rocket immunoelectrophoresis acc.to Laurell using monospecific antisera (Behringwerke AG, Marburg). In comparison with healthy subjects the patients with essential hypertension revealed statistically significant decrease in protein C antigen level (79 t 21% vs 101 ± 16; p≺0.01) and substantially increased F. VIII R: Ag values (174 ± 72% vs 103 ± 33%; p p≺0.01). No significant correlation was found between F. VIII R:Ag and protein C level. The patients had also elevation of AT III concentration ofno statistical significance. Since F. VIII R:Ag is produced and released by endothelial cells its elevated level in patients with hypertension may reflect injuryto the vascular wall. Decreased levels of protein C probably due to its increased consumption observed in the patients may contribute to imbalance in the haemostatic system and promote vascular complications.